Serge Patrice Thibodeau and the Sufi Encounter - Talbot, Émile (Studies in Canadian Literature, 2006)
Serge Patrice Thibodeau's poetry of the mid-1990s is striking as a reflection of the Acadian poet's strong attraction to Islamic spirituality and particularly Sufism. This is especially true in Le quatuor de l'errance and La traversée du désert, published jointly in 1995, and in Dans la Cité (1997). Thibodeau signals his affinity with Sufism through the epigraphs of Le quatuor de l'errance, most of which are taken from Sufi masters. The companion collection, La traversée du désert, contains no such epigraphs, but the integration of Sufi discourse is no less evident, establishing a clear continuity between the two collections that extends beyond their co-publication. The third volume, Dans la Cité, reintroduces two Sufi epigraphs (both by Ibn Arabi), interpolates Arabic script, and refers to Rumi and Ibn Arabi (along with John of the Cross) within the text.